Osimertinib inhibits brain metastases and improves long-term survival in a patient with advanced squamous cell lung cancer: a case report and literatures review - Zhang, Zhiqin; Lin, Jiamao; Yang, Linke; Li, Yang (Frontiers in Oncology, 2023)
Background Squamous cell carcinoma (SCC) is one of the most common subtypes of non-small cell lung cancer, but its treatment options remain limited. Epidermal growth factor receptor (EGFR)–tyrosine kinase inhibitors (TKIs) have limited efficacy in the treatment of lung SCC. Here, we report an SCC patient who developed EGFR-T790M mutation and showed gefitinib resistance achieved an extremely long survival by taking Osimertinib alternatively. Case summary A patient, 66-year-old non-smoking and drinking male with advanced SCC who was deemed inoperable at the time of diagnosis. The first genetic testing showed deletion mutation of exon 19 of EGFR. The patient was then treated with gefitinib with no significant efficacy. EGFR-T790M mutation was found in the second genetic test. The treatment regimen was changed to radiotherapy with Osimertinib, and the patient’s primary lesion and the brain metastases were well controlled. Conclusion This typical case highlights the important role of Osimertinib in patients with SCC carrying EGFR mutations.